Application Reception Student New At School Outside Ordinary (SLB) Pembina Pekanbaru Web based (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Since the COVID-19 pandemic has hit the world, it has made it difficult for prospective students to receive education directly, so that in 2021 the acceptance of new prospective students at the Pekanbaru Pembina State Extraordinary School is 24 prospective students, even schools that usually register new students offline or directly have now changed to online registration. The registration system at the Pekanbaru Pembina State Extraordinary School already uses an online system, namely in the form of a google form in registration and does not include uploading supporting documents. To overcome these problems, a web-based registration system is proposed. The design of this system uses the PHP and MySQL programming languages as databases, and uses the prototype method as a method of making a prospective student registration system. Modeling and system design in general use UML. With the development of a web-based registration system for prospective students, it makes it easy for parents who want to register their children to school, there is no need to come back to school in filling out registration forms or uploading the required documents. and make it easier for school principals to monitor data on prospective students who have been registered at the Pekanbaru Pembina State Extraordinary School, because this system is equipped with a feature to print data reports of registered prospective students